2013
DOI: 10.1021/jf404439b
|View full text |Cite
|
Sign up to set email alerts
|

Overview of Metabolism and Bioavailability Enhancement of Polyphenols

Abstract: A proper diet is one of major factors contributing to good health and is directly related to general condition of the organism. Phenolic compounds are abundant in foods and beverages (fresh and processed fruits and vegetables, leguminous plants, cereals, herbs, spices, tea, coffee, wine, beer) and their pleiotropic biological activities result in numerous health beneficial effects. On the other hand, high reactivity and very large diversity in terms of structure and molecular weight renders polyphenols one of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
102
0
11

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 166 publications
(113 citation statements)
references
References 190 publications
0
102
0
11
Order By: Relevance
“…In accordance with other studies, the mechanisms by which an extract can inhibit the microbial growth are varied and can be due in part to the hydrophobic nature of some of its components. These molecules can interact with the lipid bilayer of the cell membrane and affect the respiratory chain and the production of energy, leading to the interruption of intracellular signalling cascades vital for cellular functions (LEWANDOWSKA et al, 2013;CHAN-PÉREZ et al, 2016), which can affect various targets, where the different therapeutic components collaborate in a synergistic effect, having greater anthelmintic activity than the purified individual constituent (CORNARA et al, 2016). Relative to the humoral immune response, a significant rise in the total IgA was observed in the animal treated with the extract, whereas IgG level remained low in the same group when compared to control groups.…”
Section: Resultsmentioning
confidence: 99%
“…In accordance with other studies, the mechanisms by which an extract can inhibit the microbial growth are varied and can be due in part to the hydrophobic nature of some of its components. These molecules can interact with the lipid bilayer of the cell membrane and affect the respiratory chain and the production of energy, leading to the interruption of intracellular signalling cascades vital for cellular functions (LEWANDOWSKA et al, 2013;CHAN-PÉREZ et al, 2016), which can affect various targets, where the different therapeutic components collaborate in a synergistic effect, having greater anthelmintic activity than the purified individual constituent (CORNARA et al, 2016). Relative to the humoral immune response, a significant rise in the total IgA was observed in the animal treated with the extract, whereas IgG level remained low in the same group when compared to control groups.…”
Section: Resultsmentioning
confidence: 99%
“…Recent researches have shown that the phase II metabolites of genistein were not allowed to efflux among cells by a simple diffused way, which is a key step for modifying bioavailability of flavonoids [25,28,31]. Instead, they highly depend on the activity of membrane bound ATP binding cassette transport proteins (such as P-gp, MRP1, and MRP2) to over the intestinal epithelium [25,31].…”
Section: Discussionmentioning
confidence: 99%
“…Instead, they highly depend on the activity of membrane bound ATP binding cassette transport proteins (such as P-gp, MRP1, and MRP2) to over the intestinal epithelium [25,31]. A previous study has reported that efflux transporters' (P-gp, MRP1, and MRP2) expression of cancer cells is improved in a dose-dependent manner by genistein treatment for a long time [32], which would strengthen the first-pass metabolism of genistein (Figure 4).…”
Section: Discussionmentioning
confidence: 99%
“…In recent decades, it is increasingly recognized that polyphenols are often subject to rapid and extensive conjugation metabolism during the first pass across the gut/liver, and the free forms are generally not detected in the circulation (Landete, 2012;Lewandowska et al, 2013;Liu and Hu, 2007). Our previous study reported that oral emodin, an anthraquinone constituent in rhubarb, presented exclusively as emodin glucuronides in the bloodstream (Shia et al, 2010).…”
Section: Introductionmentioning
confidence: 99%